Prospective Role of Leptin Receptor Gene and its Polymorphisms on the Onset of Polycystic Ovarian Syndrome - Vanamala, Keerthi; Medithi, Srujana (Current Women's Health Reviews, 2024)
Introduction: Leptin hormone is produced by adipose tissue and soluble leptin receptor (sOB-R) influences leptin's free bioavailability. Obese individuals have unusually elevated leptin levels. Obesity influences insulin and other hormone levels and is a key risk factor for developing polycystic ovarian syndrome (PCOS) and mutations such as rs2025804 and G2548A (rs7799039). PCOS is a hormonal condition that affects females of reproductive age primarily. Although there is no known cause of PCOS, studies have linked it to various factors, including insulin resistance, obesity, and genetics. Till now, research indicates a substantial correlation between leptin and female reproductive hormones, and PCOS. Thus, the purpose of this study is to compile the available data for a better understanding of the link between leptin and its effect on female reproductive hormones and PCOS and to determine whether the leptin receptor polymorphism (LEPR) influences the start of PCOS. Methods: Following a review of the relevant papers, it was determined that there is an association between leptin and female reproductive hormones such as luteinizing hormone (LH), folliclestimulating hormone (FSH), estradiol (E2), progesterone, and prolactin. It was observed that Gln223Arg (Q223R/rs1137101), Pro1019Pro (A3057G), Lys109Arg (K109R/rs1147100), rs2025804, and G2548A (rs7799039) are the LEPR polymorphisms associated with PCOS. Gln223Arg is the most frequently studied variant in the LEPR gene across populations. Results: Interestingly, different groups demonstrated varying relationships between leptin receptor polymorphisms and PCOS, particularly for Gln223Arg, which contains two alleles (G allele and A allele). The G allele was protective against PCOS in the Korean population but increased the frequency of PCOS in countries such as Bahrain, India, Iran, and Iraq. There was no significant difference between PCOS and controls with this polymorphism in places such as China, Turkey, Saudi Arabia, and Helsinki. Conclusion: To summarize, the association between multiple leptin receptor polymorphisms and PCOS is complex and varies by research region. There hasn't been much research done on the gene polymorphism
Keywords: obese individuals